Global DNA methylation profiling in peripheral blood cells of South African women with gestational diabetes mellitus. (3rd April 2019) - Dias, Stephanie; Adam, Sumaiya; Van Wyk, Nastasja; Rheeder, Paul; Louw, Johan; Pheiffer, Carmen
Abstract: Background/Objective: Recently, several studies have reported that DNA methylation changes in tissue are reflected in blood, sparking interest in the potential use of global DNA methylation as a biomarker for gestational diabetes mellitus (GDM). This study investigated whether global DNA methylation is associated with GDM in South African women. Methods: Global DNA methylation was quantified in peripheral blood cells of women with ( n = 63) or without ( n = 138) GDM using the MDQ1 Imprint® DNA Quantification Kit. Results : Global DNA methylation levels were not different between women with or without GDM and were not associated with fasting glucose or insulin concentrations. However, levels were 18% ( p = 0.012) higher in obese compared to non-obese pregnant women and inversely correlated with serum adiponectin concentrations ( p = 0.005). Discussion : Contrary to our hypothesis, global DNA methylation was not associated with GDM in our population. These preliminary findings suggest that despite being a robust marker of overall genomic methylation that offers opportunities as a biomarker, global DNA methylation profiling may not offer the resolution required to detect methylation differences in the peripheral blood cells of women with GDM. Moreover, global DNA methylation in peripheral blood cells may not reflect changes in placental tissue. Further studies in a larger sample are required to explore the candidacy of a more targeted approach using gene-specific methylation as a biomarker for GDM in our population.